Global trends in research on eating behaviors among overweight/obese children and adolescents: a bibliometric study from 2003 to 2023 - Wang, Jiuyuan; Huang, Wenjing; Sun, Jiaqi; Yin, Saiqiong; Lin, Jiayi; Liu, Pingan; Sun, Guixiang (Frontiers in Nutrition, 2025)
BackgroundDespite the widespread interest in overweight/obese children and adolescents, there is a lack of bibliometric research on the factors influencing eating behaviors.MethodsCollated and screened research papers published between 2003 and 2023 on eating behaviors in children and adolescents affected by overweight or obesity, searched on January 1, 2024. The primary data, comprising complete records and referenced citations of publications, was extracted from the Web of Science Core Collection. Analysis of data using Bibliometrix of R package, CiteSpace, and VOSviewer.ResultsA total of 2,142 articles were included. The United States had the most publications in the field and was also the center point for world collaborations. Harvard University had the most affiliated publications, while Luis Moreno was the most prolific author. NUTRIENTS was the most published journal. High-frequency keywords included Children, overweight, physical activity, body mass index, and childhood obesity. Research trends include Epidemiology and Environment factors of obesity; Health risks associated with childhood obesity; Key eating habits and interventions for childhood obesity; Prevention and treatment of childhood and adolescent obesity.ConclusionThis research provides a comprehensive overview of global trends and key areas in studying dietary behaviors among overweight/obese children and adolescents. It offers a detailed summary of recent advancements, emphasizing this field’s critical principles and practices. By exploring these developments, the study highlights the growing importance of this research within global healthcare and suggests pathways for future research and applications.